Designing and implementing the usability engineering course based on STEAM education / Xi Cailian and Dr. Wan Ahmad Jaafar Wan Yahaya - Xi, Cailian; Wan Yahaya, Wan Ahmad Jaafar (Universiti Teknologi MARA, Kedah, 2023)
In this article, we introduced the characteristics and advantages of STEAM education, and discussed the problems faced by the "usability engineering" course. We put forward three principles of curriculum design: comprehensiveness, innovation, and feasibility. According to these principles, we integrated STEAM education into this course, and designed and implemented this course with Project-Based Learning (PBL) method as the carrier. We found that students had improved their learning engagement and motivation in this process. And their final works quality, comprehensive ability and team cooperation ability have improved. This study confirmed the feasibility of STEAM education applied to university course design. In the part of teaching reflection, we made suggestions for further improvement of course design for further research.